"After Philando, I Had to Take a Sick Day to Recover": Psychological Distress, Trauma and Police Brutality in the Black Community. Issue 9 (29th July 2022) - Hawkins, Deion S.
ABSTRACT: Unfortunately, encounters between Black Americans and law enforcement frequently feature violence, resulting in a myriad of negative health influences including increased rates of race-based mortality, chronic stress and trauma. Despite police brutality's increased media coverage, there is a dearth of empirical research surrounding violence at the hands of law enforcement and how it impacts the health of the Black community. Police departments across the country fail to release official data or information related to police brutality; however, technological advancements, such as social media and smart phones, have revolutionized information seeking and dissemination related to brutality. Drawing on Critical Race Theory (CRT), this qualitative study used phenomenological interviews to better understand how Black Americans interpret stories of police brutality and the impact such stories have on one's mental health. Analysis confirmed previous quantitative research, revealing the Black community can be traumatized by viewing graphic images or videos of police brutality. Interviewees reported a constant fear of dying, hyper alertness and lack of coping mechanisms. Findings from this study not only should be used to build health communication models that can address mental health issues, but also should be used as a blueprint to improve police-community relations. Implications are drawn from this study for addressing the issue of police violence in the Black community. Policy recommendations are suggested.